MY SAY: Nurturing a KIP culture - Abd Razak, Dzulkifli (2010)
Move over BRIC (Brazil, Russia, India, China). Now, it's time for the PIIGS (Portugal, Italy, Ireland, Greece, Spain). Of the PIIGS, Greece is very much in the limelight, perhaps for the wrong reasons. Right or wrong, there is always a lesson to learn, that is, key intangible performance (KIP). What seems clear is that the trail of flawed practices of America's toxic banking and financial institutions is now visible in other parts of the world, with Greece being a case in point. In some respects, it is reminiscent of the outrage that the US banking sector created recently. As the crisis deepens, this becomes even clearer, despite being cleverly camouflaged by an unscrupulous institution until recently.